Privacy-Preserving Data Mining: - Aggarwal, Charu C. (Springer, 2017)
Advances in hardware technology have increased the capability to store and record personal data about consumers and individuals. This has caused concerns that personal data may be used for a variety of intrusive or malicious purposes.